Language, citizenship, and Sámi education in the Nordic North, 1900-1940 - Kortekangas, Otso, 1987- (McGill-Queen's Indigenous and northern studies, 2021)
"In the making of the modern Nordic states in the first half of the twentieth century, elementary education played a paramount role in creating a notion of citizenship that was universal and equal for all citizens. The elementary education policies ignored, in most cases, the language, culture, wishes, and needs of minorities such as the Indigenous Sámi. Presenting the Sámi as an active, transnational population in early twentieth-century northern Europe, Otso Kortekangas examines how educational policies affected the Sámi people residing in the northern parts of Norway, Sweden and Finland. In this detailed study, Kortekangas explores what the arguments were for the lack of Sámi language in schools, how Sámi teachers have promoted the use of their mother tongue within the school systems, and how the history of the Sámi compares to other Indigenous and minority populations globally. Timely in its focus on educational policies in multiethnic societies, and ambitious in its scope, the book provides essential information for educators, policy-makers, and academics, as well as anyone interested in the history of education, and the relationship between large-scale government policies and Indigenous peoples."--